(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2026)
This study’s main objective was to analyze the development of a didactic sequence focused on experimental activities for the contextualized teaching of chemistry. To achieve this, we explored the production of bioplastics from Amazonian tuber peels, using Problem-Based Learning (PBL) as the methodological approach. During the activities, students experienced the bioplastic manufacturing process firsthand, which allowed for the application of concepts such as polymerization, molecular interactions, and material properties. Besides deepening their understanding of the chemical principles involved, this experience broadened students’ awareness of environmental and social issues related to plastic use. Therefore, this experimental activity represents an excellent opportunity to integrate various chemistry concepts, offering students a holistic and practical understanding of science, in addition to promoting sustainabilit.